Analysis of Hybrid Agile Project Management in the Telecommunications Industry - Nehir Tokgöz; Svitlana Samoylenko; Shiv Kumar Tripathi; Betül Aydin (İşletme Bilimi Dergisi)
This paper explores Hybrid Agile Project Management in the telecommunications industry, focusing on the motivation behind the adopting hybrid methods, collaboration, and conflicts between Agile teams and Project Managers. The primary objective is to evaluate the company’s current state, identify strengths and weaknesses, and provide recommendations for improvement. The research employs a qualitative approach, conducting interviews with key participants such as PMOs, Project Managers, Agile Analysts, Product Owners, Scrum Masters, and Agile Coaches. This approach provided comprehensive insights into the case company’s agile practices, highlighting the complexity of its organizational structure and the impact on project management. The thematic analysis of these interviews emphasized the hybrid approach's role in balancing regulatory, security, and business needs. The findings reveal that although Agile, particularly the Scrum methodology, is central to the company's operations, the hybrid approach plays a key role in addressing the challenges of continuous improvement and flexibility. The company integrates Agile with project management through distinct roles such as Analyst Phase Leader (APL) and Development Phase Leader (DPL), which help mitigate resource management issues and regulatory constraints that can cause conflicts. The company has developed customer frameworks and an adaptive approach to resolve these. TOGAF and PMI have also been aligned with Agile practices to support large-scale enterprises. The paper concludes that Agile satisfaction tends to decrease as company size increases, particularly in the telecom sector, making this research valuable due to its unique recommendations for improving hybrid project management in complex, large-scale environments.